408 - Muscle strength is an important predictor for limitations in basic activities of daily living among people with severe disability. (October 2021) - Wang, Jinni; Wu, Jialan; Liang, Lizhu; Ye, Rui; Liao, Xiaoyan
Abstract : Objective: This study aimed to identify predictors of limitations in basic activities of daily living (BADL) among people with severe disabilities. Methods: 4075 long-term care beneficiaries with severe disabilities in Guangzhou, China, were included during July 2018 and March 2019. BADL was assessed using the Barthel index (BI). Muscle strength was measured by using the Lovett Rating Scale. Age, gender, comorbidities, and muscle strengths were collected as independent variables. Chi-square Automatic Interaction Detector (CHAID) method was used to examine associations between independent variables and item scores of the BI. Results: Muscle strength and history of stroke were parent node and child node for most of BADL limitations, respectively. Upper limb muscle strength (≤ 3) was a major predictor for dependence in feeding, grooming, toileting, dressing, and transfer, while lower limb muscle strength (≤ 3) was a major predictor for limitation in mobility. Conclusions: Muscle strength was the strongest predictor of BADLs among people with severe disability. Muscle strength grading may be optimal for designing supporting strategies for people with severe disabilities.